MINYAK JARAK EPOKSI SEBAGAI BAHAN PELUNAK UNTUK PEMBUATAN KOMPON RUBBER WASHER - Rahmaniar, Rahmaniar (Jurnal Dinamika Penelitian Industri, 2010)
The research objective was to determine a proper formulation in rubber compound processing by addition of jarak oil epoxy to make rubber washer compound the quality specification.The experimental design used in this study was Complete Randomized Design (CRD) with two replications and two factors. The first factor was the concentration of epoxidized castor oil (P1 : 3 phr, A2 : 2 phr and A3 : 3 phr). The tested parameters were hardness, elongation at break, abrasive resistance and flex resistance, The result showed that the addition castor oil and antioxidants and its interaction had significant effect on the elongation at break and abration resistance. The addition of epoxide castor oil gave insignificant effect on the hardness of the rubber compound. The best treatment was found at epoxy castor oil concentration of 3 phr and antioxidant of 3 phr having characteristic of rubber washer compound that consisted hardness 48 Shore A, elongation at break 2682%, abrasive Resistance 131 DIN mm and flex resistance : no flex.